PENGARUH PRAKTEK-PRAKTEK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA PT. BIN YAFIL AL-ALAM - Supriyadi, Supriyadi (Journal MISSY (Management and Business Strategy), 2023)
This study aims to analyze the effect of human resource practices on employee performance at PT. Bin Yafil Al Alam. This type of research is associative which aims to determine the influence or relationship between two or more variables. The number of respondents as many as 35 people. The analytical tool used is multiple linear regression (SPSS version 22). The results of this study indicate that human resource management practices have a significant effect on employee performance at PT. Bin Yafil Al Alam.